Value engineering study on curtain walling system - Tan, Chun Li. (2008)
Curtain wall systems have now become an essential feature of modern architecture. Every curtain wall has to be designed in relation to local climatic and atmospheric conditions, the particular function of the building it encloses and certain economic factors.